1995
DOI: 10.1164/ajrccm.152.6.8520746
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of stepwise CPAP titration. Behavior of respiratory and neurological variables.

Abstract: Because successful medical treatment of obstructive sleep apnea/hypopnea syndrome (SAHS) depends on adequate CPAP treatment, we have analyzed in nine SAHS patients the behavior of respiratory and neurological parameters during a stepwise, polysomnography-controlled CPAP titration to achieve an optimal CPAP. Particularly, we have focused on which simple variable could predict the optimal CPAP pressure and could better define a distinctive optimal-suboptimal pattern. Main parameters analyzed through the CPAP tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 0 publications
2
53
0
6
Order By: Relevance
“…Although a recent study found that during nCPAP titration arousals stopped before oesophageal high swings [30], we do not know what happens when the initial sleep deprivation is less acute. After having completed their slow wave rebound, patients may become more arousable and, due to its excessively low pressure level, nCPAP may convert obstructive sleep apnoea to airway resistance syndrome.…”
Section: Discussionmentioning
confidence: 79%
“…Although a recent study found that during nCPAP titration arousals stopped before oesophageal high swings [30], we do not know what happens when the initial sleep deprivation is less acute. After having completed their slow wave rebound, patients may become more arousable and, due to its excessively low pressure level, nCPAP may convert obstructive sleep apnoea to airway resistance syndrome.…”
Section: Discussionmentioning
confidence: 79%
“…2) by the fact that the nonlinear relationship V'th-V' depends on the frequency and on the waveform of the breathing flow. This may particularly affect the detection of obstructive hypopnoeas, since in this case the inspiratory flow tends to change from a quasisinusoidal (normal breathing) to an almost square-wave pattern [11], which, according to figure 4, tends to further underestimate hypopnoeas. As illustrated in the example in figure 2 (left and right), change from a sinusoidal pattern to a square-wave flow of 50% amplitude results in a change of only 5% in thermistor signal.…”
Section: Discussionmentioning
confidence: 99%
“…The thermistor/thermocouple was exposed to realistic flow amplitudes ranging from values typical of normal breathing (±0.8 L·s -1 ) to those of severe hypopnoeas (±0.05 L·s -1 ) and for frequencies (10,15 and 20 bpm) within the range of observed respiratory frequencies. Moreover, we tested two different airflow waveforms (sinusoidal and square-wave) to assess the response of the thermistor when subjected to changes of breathing pattern such as those found in patients from normal breathing to the typically flow-limited airflow during obstructive hypopnoeas [11].…”
Section: Discussionmentioning
confidence: 99%
“…the lowest pressure that achieves a therapeutic result during an entire night), or "CPAP titration", has traditionally been conducted by a technician in the sleep laboratory during full polysomnography [2,3]. Although this procedure was initially exclusively directed towards eliminating only frank apnoeas and hypopnoeas, it is now common for the sleep technician to titrate CPAP first to the abolition of apnoeas and hypopnoeas, then to the elimination of snoring, intermittent oxygen desaturations and microarousals on electroencephalogram (EEG) [3,4]. Until recently, CPAP titration was always carried out in the sleep laboratory, but this is a costly and labour-intensive procedure.…”
Section: P Lévy J-l Pepinmentioning
confidence: 99%